Efficacy of progressive relaxation technique and yoga in patients with stress-induced asthma: A randomized controlled trial - S Veena Kirthika; K Padmanabhan; S Sudhakar; C V Senthil Nathan; S Ramachandran (Wolters Kluwer Medknow Publications, 2018)
Background: Asthma is a chronic inflammatory disorder of the airway. In susceptible individuals, this inflammation causes recurrent episodes of wheezing, breathlessness, and coughing. Various physiotherapy techniques help in the reduction of symptoms associated with asthma which includes deep breathing exercises and relaxation postures. Progressive relaxation technique (PRT) is useful in reducing the respiratory symptoms and stress in asthma. Yoga techniques have shown clinically relevant improvements in their quality of life and effective reduction in the frequency of attacks and degree of stress. Objective: The objective of this study is to compare the effect of PRT and yoga in patients with stress-induced asthma (SIA) so that better treatment program can be adopted in the reduction of symptoms in participants with SIA. Methodology: Thirty participants with asthma were recruited for the study and were divided into two groups. Group A (n = 15) was treated with PRT and Group B (n = 15) was treated with yoga technique for a duration of 3 months. Outcome Measures: Asthma Quality of Life Questionnaire (AQOL) and Depression, Anxiety and Stress Scale (DASS) were used. Results: Group B (yoga group) showed a significant difference, P < 0.05 in the mean values of DASS and AQOL when compared to Group A (P > 0.05). Postyoga intervention, the patients with SIA demonstrated decrease in the symptoms of depression, anxiety, and stress, and increased quality of life. Conclusion: Three-month duration of yoga is more effective than PRT in patients with SIA in reducing asthmatic symptoms and improving quality of life.